Assessing English Students` Vocabulary Size of Lampung State Islamic University - Iwan Kurniawan (Bina Nusantara University, 2017)
The aims of this research were to measure the English students’ vocabulary size as well to measure the students’ vocabulary size which was less and more than 1000 words. The research method that the researcher used was quantitative with 209 students as sample. The research instrument was a test which consisted of 79 items. The research findings show the first year students of UIN Raden Intan English department have an average vocabulary size 1400 words. The number of the first year students of UIN Raden Intan English department who have the vocabulary size less than 1000 words is about 11 students or only 6% students. On the other hand, the number of students who have the vocabulary more than 1000 words is about 192 students or 94% students.